Training physicians in shared decision-making: who can be reached and what is achieved? - Bieber, Christiane; Nicolai, Jennifer; Hartmann, Mechthild; Blumenstiel, Klaus; Ringel, Nadja; Schneider, Antonius; Härter, Martin; Eich, Wolfgang; Loh, Andreas (Patient education and counseling, 2009)
OBJECTIVE: To report on experiences with a general shared decision-making (SDM) physician training program offered to physicians throughout Germany. - METHODS: This study enrolled 150 physicians in an 8-h SDM training program. Physicians were assessed with standardized instruments before and after training. Main variables of interest were physician professional attributes, personality characteristics, attitudes, measures of training success (quality rating, knowledge, competency ratings), and variables associated with training success. - RESULTS: The SDM training obtained positive quality ratings, led to an amelioration in an objective SDM knowledge test (p<.001), and highly improved physicians' confidence in their SDM competencies (p<0.001). It attracted experienced, middle-aged (45 years), male and female (46%) physicians, mostly office-based (2/3) general practitioners and internists (2/3). Most physicians (94%) reported positive attitudes towards SDM. They were securely attached (63%) with predominant social career choice motives (46%). Physicians with personality characteristics clashing with the SDM concept benefited mostly from the training. - CONCLUSION: A voluntary SDM training program is attractive to practicing physicians and effective in increasing SDM-related confidence and knowledge. - PRACTICE IMPLICATIONS: Even physicians who are highly motivated to use SDM can improve their skills and benefit from SDM training. The dissemination of SDM training programs should be encouraged.
Gesehen am 04.01.2023